Project-Based Learning in Elementary School: Influence on Students' Creative Thinking Ability - Muhammad Rizky Pratama; Ulya Fawaida; Rica Mae Guarin (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2023)
This research is experimental research with a quantitative approach that aims to "determine the effect of a project-based learning model on students' creative thinking skills by making a herbarium. In this study, the sample used was 51 students. The data collection techniques used in this study were tests and documentation. The results showed that "the experimental class had an average posttest score of 72.47 and the control class had a posttest average score of 57.53. The results of the creative thinking skills of the experimental class for indicators of fluency were 79%, flexibility 71%, originality 73%, and elaboration 56%; the control class had an average value for each indicator which was lower than the experimental class. This study’s results indicate an "influence in the use of the project-based learning model through making a herbarium on the creative thinking skills of students in grade 4 MI NU Miftahul Ulum Loram Kulon. The effect of the project-based learning model on students' creative thinking skills is evidenced by the regression equation Y=18.802 + 0.933X. The existence of this project-based learning model has a positive and significant relationship of 0.877 which is included in the very strong category and can contribute to students in improving students' creative thinking skills by 76.9%.